Revisitar Vieira no séc. XXI - Cultura Política e Atualidade Vol. I - José Eduardo Franco (Outros Títulos, 2020)
"If we revisit Father António Vieira in the 21st century, we inevitably recognize in him the plurality of approaches [...]: first of all, he was (and is) a thinker of our culture and of the politics of his time, developing themes that demarcate what we call his actuality; and it is certainly not banal to trace a sense of actuality evident in those who lived, thought, preached and wrote over three centuries ago. That is so, but it is not just about that. The legacy of Father Antonio Vieira is also projected, until today, in our language, in the imaginary of his great cultists, in the arts and in his presence in the educational system. The texts we can read here attest well to what is said: the image of Vieira in our historiography, the epistolography and his cult, the prophetic work and the questions to which he invites, the audacity of theological thought, the path of life (a path that made this great figure almost a character of fiction, as the cinema confirmed), the political intervention to which he did not dodge, the unparalleled contribution he gave to sacred oratory".